Perancangan Ulang Identitas Visual Merek “Kopi Manglayang” untuk Masyarakat Usia 20-30 Tahun di Kota Bandung - Diwan Setiawan; Siti Jaenab (Universitas Informatika dan Bisnis Indonesia, 2023)
Coffee is one of the drinks often consumed by the people of Indonesia. Nowadays, it become a lifestyle among communities. Manglayang Coffee is an SMEs founded in 2011 by Mr. Dadan R Wijaya, located in Panjalu Village, Bandung Regency. Manglayang Coffee is a product of collaboration between Manglayang Coffee and Forest Farmers Groups in the West Manglayang BKPH Perhutani area. In developing a company, a company must have a visual identity as a differentiating factor from other companies, which is emphasized in the form of perceptions, images and graphics. Three aspects must have characteristics that align with the company to become a high-quality and capable brand. This study applies a qualitative method using interviews, observation, questionnaires and document studies to obtain the data. The results of this study indicate that the existence of Manglayang Coffee Products lacks of interest to the public. According to the results of questionnaires in the community, 97% of respondents answered that they (did not know) needed to learn about the existence of Manglayang Coffee products, due to the weak visual identity of Manglayang Coffee products, seen from weak visuals and the use of long designs. Given the continuing competition, the Manglayang Coffee company needs to make changes or redesigns starting from the visual identity in the form of a logo, advertising media/visual communication media. That is an important thing attract consumers, improve the image and position of the company.